Management of grade I vaginal prolapse in a Friesian cross: a case report - Abdullah, Faez Firdaus Jesse (International Organization of Scientific Research, 2014)
A 350kg Friesian cross was presented to the Veterinary Teaching Hospital, University Putra Malaysia with a complaint of a bulging vagina one month after paturition. On physical examination, there was evidence of a grade I vaginal prolapse with presence of a yellowish mucoid secretion from the vulva. All the vital parameters were normal. Blood workout showed leucocytosis accompanied by neutrophilia with left shift, lymphocytosis and monocytosis. Creatine kinase was elevated ten folds, while serum globulin was only slightly elevated. There was a slight decline in calcium level in the blood. The prolapse was corrected surgically by applying Buhner’s suture. Systemic analgesic, antibiotic, multivitamin and calcium infusion were administered to minimize pain, prevent bacterial complication and normalize the calcium level in the blood, respectively. The prognosis was good and the prolapse regressed completely after a week. Prompt and timely management of vaginal prolapse is necessary in order to avoid serious complications that may predispose to uterine infections, infertility and death due to septicemia.